2017
DOI: 10.1158/1055-9965.epi-16-0341
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Population-Level Genotype Data with Functional Annotation Reveals Over-Representation of Long Noncoding RNAs at Ovarian Cancer Susceptibility Loci

Abstract: Background Genome wide association studies (GWAS) have identified multiple loci associated with epithelial ovarian cancer (EOC) susceptibility, but further progress requires integration of epidemiology and biology to illuminate true risk loci below genome-wide significance levels (P<5×10−8). Most risk SNPs lie within non-protein-encoding regions, and we hypothesize that long non-coding RNA (lncRNA) genes are enriched at EOC risk regions and represent biologically relevant functional targets. Methods Using im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…network) for follow-up validation. This strategy has been demonstrated as being effective in previous studies [ 75 , 76 ]. Taken together, regulatory analysis could prove an important addition to many upcoming PheWAS and GWAS, especially for the studies without large population sizes.…”
Section: Discussionmentioning
confidence: 94%
“…network) for follow-up validation. This strategy has been demonstrated as being effective in previous studies [ 75 , 76 ]. Taken together, regulatory analysis could prove an important addition to many upcoming PheWAS and GWAS, especially for the studies without large population sizes.…”
Section: Discussionmentioning
confidence: 94%
“…Deregulation of some miRNAs, such as miR-509-3p and miR-211, through HR inhibition, has been implicated in platinum-sensitive (Pt-S) cancers [ 50 , 51 ]. Long noncoding RNAs (lncRNAs), which exhibit a wide range of physiological functions, such as transcription regulation and scaffolding within cells, have been linked to OC risk, carcinogenesis and prognosis [ 52 , 53 ]. For instance, PCAT -1 leads to HRD in prostate cancer by suppressing BRCA2 [ 54 ].…”
Section: From Ovarian Cancer Genetics To Homologous Recombination Def...mentioning
confidence: 99%
“…The variability in genes encoding lncRNAs also plays an important role in the function of these non-coding elements. GWAS of approximately 18,000 invasive OC and 34,000 control samples of European ancestry revealed that invasive OC behavior was associated with 5294 SNPs, of which 1464 SNPs were mapped to 53 lncRNA genes [ 120 ]. Among particular genetic variants, SNP rs17427875 (minor T allele) in lncRNA HOXA11-AS1 is associated with reduced tumor growth in an in vivo mouse xenograft model based on the OC C13 cell line [ 121 ].…”
Section: The Role Of Non-protein-coding Transcripts and Their Role In The Development Of Ovarian Cancer Metastasismentioning
confidence: 99%